Dušan Bandić – context, opus, significance - Ivan Kovačević (Etnoantropološki Problemi, 2016)
The scientific opus of Dušan Bandić is viewed through the context and time frame in which he started researching folk religion in order to, through the analysis of his most important texts, arrive at the conclusion about the importance of his opus for the modernization of Serbian anthropology. This is just one segment, although the most important one, of the evaluation of the significance of an opus for the history of Serbian anthropology. Other aspects of action, which refer to institutional positioning and activity as well as one’s social and political life and ultimately the consequences such actions had are significant for the history of science, but are not encompassed by this paper. The paper deals with the description of the context and state of research into folk religion at the beginning of Bandić’s career and the general knowledge about global anthropological trends in Serbian ethnology at the time. Afterwards the focus is shifted to the contents of his work through viewing the larger ideas and methodological systems present in Bandić’s work – evolutionism, functionalism and structuralism, in order to, ultimately, come to a conclusion about the development of methods which Bandić applied, as well as the place which his opus occupied in a crucial time for Serbian ethnology.